THE AUGUSTAN AGE IN ENGLISH LITERATURE: ALEXANDER POPE’S SATIRICAL STYLE AND SOCIAL CRITICISM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is devoted to the Augustan Age (the first half of the eighteenth century) in English literature and to the social criticism and satirical style of its central poet, Alexander Pope. Augustan literature sought to reflect ideals of reason, order, and civic virtue. Pope, the most influential poet of this period, perfected the “Heroic Couplet” and used satire to expose the vanity, superficiality, and moral corruption of his society. In The Rape of the Lock, he mocks the aristocratic class for giving excessive importance to trivial matters, creating one of the finest examples of the mock-epic genre. Through his works, Pope defends the principles of order and rationality while offering moral instruction against the artificiality and frivolity of his age.